Wind tunnel test on mean wind forces and peak pressure acting on ellipsoidal nacelles of wind turbine. Issue 2 (April 2022) - Noda, Hiroshi; Ishihara, Takeshi
Mean wind forces and peak pressures acting on ellipsoidal nacelles are investigated by wind tunnel tests. The wind force coefficients of the ellipsoidal nacelles for the wind turbine design and the peak pressure coefficients for the nacelle cover design are proposed based on the experimental data. The wind force coefficients are expressed as functions of yaw angles. The proposed formulas are compared with Eurocode, Germanischer Lloyd and ASCE7-16. It is found that the mean wind force coefficients for the wind turbine nacelles are slightly underestimated in Eurocode. The equivalent maximum and minimum mean pressure coefficients are proposed for use in Design Load Case 6.1 and Design Load Case 6.2 of IEC 61400-1. The peak pressure coefficients are derived using a quasi-steady theory. The proposed equivalent maximum and minimum mean pressure coefficients are much larger than those specified in Germanischer Lloyd.